Improvement of Rolling Method in Dust Removal of Ceiling Fan - Muhammad Khairul Aiman Norhisham; Muhammad Iqbal Aizad Maznuri; Ekmal Alif Kamal Abd Harith; Hassim, Hairul Mubarak (Multidisciplinary Applied Research and Innovation, 2024)
Small particle such as dust, dirt and pollen accumulate on oscillating fan. There is a need of creating a fan ceiling cleaning tool that not only to simplify the fan cleaning process and to reduce the cleaning time. Most of the market uses full human power for Ceiling Fan Cleaning Tool. In addition, the materials and designs in the market are of poor quality and easy to damage. A power motored rotating microfiber material is introduced. Dust statically attached to the microfiber while rotating the microfiber causes dust to fall into a dust container. It is found that the rotating speed of ceiling fan increases by 1.2% to 5% after the ceiling fan blade is cleaned by the cleaning tool.